Description of abnormal uterine cervical citology in Armenia - Quindío in 2012 (Revista de Investigaciones Universidad del Quindío, 2017)
Although there is a screening test that allows early detection of cervical cancer, many women do not do it. Specifically in women of Armenia, there are no studies showing the current status of implementation of cervical cytology.Objective: To describe the results of cytology reports made in 2012 and contribute to the construction of the base line of the Ten-Year Health Plan for Armenia. Methods: A descriptive cross-sectional study, conducted hand in hand with the Secretary of Health, which provided information and application for systematization. A random sample of all cytology reports were taken, and the information was analyzed and systematized.Results: We found that women were aged between 15 and 79 years; the average was 37.4 years old. The most reported result was cellular atypia (ASC-US) (76%). The most commonly recommended treatment was colposcopy + biopsy (36.05%); 22.37% of those women were not using any contraceptive methods. Quindicancer was the institution that performed most of the cytology (20.79%) and cellular atypia resulted frequently reported the treatment with colposcopy + biopsy (25.79%). The 16.05% of women with this result did not use any contraceptive method and only 1.52% used condom. Conclusion: Women in Armenia presented a higher percentage of cellular atypia and colposcopy + biopsy were advised as indicated in literature, most of the did not use contraceptive methods and only 1.52% who did the cytology used condom
Keywords: uterine cervical cytology; abnormality in cytology